표준어와 방언의 줄다리기 ― 말레이시아 중국계 사회 내부 언어 위상 변화에 대한 통시적 고찰 - 소열녕; Seow Yuening (중국학보, 2025)
이 논문은 말레이시아 중국계 사회에서 표준어와 방언의 위상 변화를 가정·공공장소·교육·방송의 네 가지 영역으로 나누어 시기별로 분석하였다. 특히 Ferguson(1959)의 양층 언어 현상(diglossia)개념을 틀로 삼아 H(high)-L(low) 구조의 시대적 변화를 검토하였다. 1912년 이전 ‘순수 방언 시기’에는 모든 영역에서 방언이 사용되었고 방언 간 접촉으로 인해 지역방언이 상층어(H), 그 하위 방언이 하층어(L)로 기능하였다. 1912년 ‘국어 시기’의 도래와 함께 중국본토의 ‘국어운동’ 영향으로 화문학교에서 표준어 교육을 본격적으로 도입하였고 모든 교과목을 표준어로 가르치기 시작하였다. 1946년에 개국한 말라야방송은 표준어와 방언 프로그램을 병행 편성하여 방송 영역에서 방언이 H 기능을 수행할 여지를 남겼다. 1957년 말라야 독립 이후 중국계 이민자들은 ‘화교'에서 ‘중국계[華人]'로 신분이 전환되면서 ‘국어’는 말레이어를 의미하게 되었고 표준 중국어는 ‘화어’로 명칭이 바뀌었다. 이 시기부터 ‘화어’는 방언을 제외한 개념으로 축소되고, 표준어와 방언을 통칭하는 용어는 사라졌다. 1980년대 이후 표준어 보급 캠페인이 민간 주도로 전개되었고 화문학교에서는 방언 사용 금지 규정이 시행되었다. 방송에서는 점차 방언 프로그램들이 줄어들고 국영방송에서는 표준어 위주로 편성이 이루어졌다. 이에 따라 방언은 교육과 방송뿐만 아니라 가정과 공공장소에서도 점진적으로 사용이 줄어들기 시작하였다. 2010년대 이후에는 방언 소멸 위기에 대한 사회적 경각심이 확대되었고 방언 살리기 운동이 민간중심으로 전개되었다. 페낭에서 시작된 ‘민남 방언 살리기 캠페인’, 복건회관의 방언 스토리텔링 대회, 국립말라야대의 방언 페스티벌 등은 방언의 사회적 위상 회복을 위한 노력의 일환이라고 할 수 있다. 결론적으로 표준어의 위상은 강화되어 현재 거의 모든 영역에서 H를 독점하고 있으며 방언은 그 사용 영역이 축소되고 있으나, 최근 들어 문화·정체성 보존 차원에서 재조명되고 있다. 방언 사용은 단지 언어의 문제를 넘어 중국계 내부의 ‘작은 정체성’ 유지와 직결된 문화적 과제로 자리매김하고 있다. This paper examines the historical shift in the relative status of Standard Chinese(Mandarin) and Chinese dialects within the Chinese Malaysian community, focusing on their use across four domains: home, public spaces, education, and broadcasting. Adopting Ferguson’s (1959) framework of diglossia, the study traces the transformation of the H(high)-L(low) relationship over time. In the period prior to 1912, which is the “pure dialect era,” Chinese dialects were used exclusively in all spheres of daily life. Contact among different dialect groups led to an internal hierarchy, with dominant regional dialects occasionally functioning as high variants(H) and more localized dialects as low variants(L). The onset of the “Guoyu era” in 1912, marked by the influence of China's national language movement, introduced Standard Chinese into Chinese-medium schools as the medium of instruction, gradually replacing dialects in educational settings. The establishment of Radio Malaya in 1946 further institutionalized the use of Standard Chinese, while still maintaining dialect programming, thus allowing dialects to retain their presence in the H domain. Following Malaya’s independence in 1957, the identity of Chinese residents shifted from “Overseas Chinese” (Huaqiao) to “Malayan Chinese” (Huaren). As Malay was designated the national language, the term “Guoyu” could no longer be applied to Chinese, prompting a terminological shift to “Huayu”. However, “Huayu” increasingly came to refer specifically to Standard Chinese, excluding dialects. This redefinition created a conceptual void, as no inclusive term remained to refer to both standard and nonstandard varieties of Chinese. The 1980s saw the launch of the Speak Mandarin Campaign, initiated by community organizations rather than state policy. During this period, Chinese schools began enforcing bans on dialect use, and dialect programming in state-owned radio station was significantly reduced. As a result, the use of dialects declined not only in formal settings but also in the home and in public life, where Standard Chinese gradually gained ground. Since the 2010s, growing awareness of dialect endangerment has sparked a range of preservation efforts. Initiatives such as Penang’s “Speak Hokkien Campaign”, dialect storytelling contests hosted by local Chinese associations, and the Chinese Dialect Festival organized by the Department of Chinese Studies, University of Malaya have aimed to revitalize interest in regional speech varieties and promote intergenerational transmission. In sum, while Standard Chinese now occupies a dominant position across virtually all domains, dialects are experiencing renewed attention as important markers of cultural identity. The preservation of dialects is increasingly framed not only as a linguistic concern but as a key component of sustaining localized forms of Chinese Malaysian identity.